Tindak Tutur Direktif dalam Film Jumbo Karya Ryan Adriandhy: Kajian Pragmatik terhadap Interaksi Tokoh dan Perkembangan Alur Cerita - Lailatul Fitriyah; Ria Kasanova (Jurnal Pendidikan Indonesia, 2026)
Directive speech acts in films play an important role in constructing character interactions, character development, and narrative dynamics. However, pragmatic studies examining directive speech acts in Indonesian animated children’s films remain relatively limited. This study aims to analyze the forms and pragmatic functions of directive speech acts in the film Jumbo by Ryan Adriandhy. This research employed a descriptive qualitative approach using Searle’s theory of directive speech acts. The research data consisted of inter-character utterances in the film Jumbo, collected through observation and note-taking techniques, and analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings revealed 96 instances of directive speech acts, consisting of ordering, requesting, suggesting, advising, and challenging forms. Ordering speech acts were the most dominant form, indicating that communication patterns among characters in the film were constructed through both instructive and collaborative interactions. Pragmatically, directive speech acts in Jumbo function not only to direct characters’ actions, but also to build emotional relationships, social solidarity, character education, and narrative development. The findings demonstrate that the use of directive speech acts in children’s films can serve as a medium for fostering empathy, courage, cooperation, and polite communication through character interactions.